In vitro antifungal activity of topical and systemic antifungal drugs against Malassezia species - Carrillo Muñoz, Alfonso Javier (2013)
The strict nutritional requirements of Malassezia species make it difficult to test the antifungal susceptibility. Treatments of the chronic and recurrent infections associated with Malassezia spp. are usually ineffective. The objective of this study was to obtain in vitro susceptibility profile of 76 clinical isolates of Malassezia species against 16 antifungal drugs used for topical or systemic treatment. Isolates were identified by restriction fragment length polymorphism. Minimal inhibitory concentrations (MIC) were obtained by a modified microdilution method based on the Clinical Laboratory Standards Institute reference document M27-A3. The modifications allowed a good growth of all tested species. High in vitro antifungal activity of most tested drugs was observed, especially triazole derivatives, except for fluconazole which presented the highest MICs and widest range of concentrations. Ketoconazole and itraconazole demonstrated a great activity. Higher MICs values were obtained with Malassezia furfur indicating a low susceptibility to most of the antifungal agents tested. Malassezia sympodialis and Malassezia pachydermatis were found to be moresusceptible species than M. furfur, Malassezia globosa, Malassezia slooffiae and Malassezia restricta. Topical substances were also active but provide higher MICs than the compounds for systemic use. The differences observed in the antifungals activity and interspecies variability demonstrated the importance to studying the susceptibility profile of each species to obtain reliable information for defining an effective treatment regimen.